Soft switching maximum power point tracker with resonant switch in PV system - Oncu, Selim; Nacar, Salih (Elsevier BV, 2016)
Abstract Conventional boost converters are used in many applications such as power factor correction, electronic ballasts, battery chargers, photovoltaic (PV) applications. PV systems need maximum power point tracker (MPPT) to have efficient power conversion. Maximum power point trackers are usually implemented by pulse width modulation (PWM) controlled converters. In PWM control, the switching losses and the voltage–current stresses of the device increase. In the present paper, an MPPT with soft switching boost converter is designed, simulated and experimentally tested. The topology adds a resonant network to the conventional boost converter and controls the PV power by changing the switching frequency. In the proposed converter, Perturb & Observe method is used as power tracking algorithm that is implemented with dsPIC30F2020 and zero voltage switching (ZVS) is achieved in wide range. The variable frequency controlled MPPT is tested for different radiation levels and loads and switching characteristic is compared with PWM controlled boost converter. The proposed single switch resonant converter is simulated in PSIM and experimental validation is also given for a 40 W PV generation system.
Keywords: 7. Clean energy